The Major Solar Energetic Particle Event on 2024 May 20: Multispacecraft Observations of a Long-lasting Energetic Particle Reservoir - Lario, D.; Hu, J.; Balmaceda, L. A.; Kwon, R. Y.; Wallace, S.; da Silva, D. E.; Mays, M. L.; Krupar, V.; Carcaboso, F.; Warmuth, A.; Stiefel, M. Z.; Khoo, L. Y.; et al. (Institute of Physics Publishing, 2026)
The fleet of spacecraft distributed across the inner heliosphere during 2024 May–June provided a unique opportunity to analyze, over a broad range of heliolongitudes, the effects produced by the complex sunspot group associated with Active Region 13664. The intense solar activity from 2024 May 8 to 2024 June 21 produced unusually elevated solar energetic particle (SEP) intensities observed at heliocentric distances ≲1 au by Solar Orbiter, Parker Solar Probe, STEREO-A, and near-Earth spacecraft. This activity resulted in a >40 day period of enhanced ≲10 MeV proton intensities spanning at least ∼170° in longitude. Among these events, the 2024 May 20 SEP event was remarkable for its high intensity and wide spatial extent. It was associated with a fast (≳1500 km s−1) halo coronal mass ejection (CME) and an X16.5 solar flare located ∼171° in longitude from Earth. Near Earth, the event produced a long-lasting ∼100 MeV proton intensity enhancement with energy spectra flattening between 30 and 80 MeV. It also led to the formation of an energetic particle reservoir that persisted for ∼2 weeks and extended across at least ∼170° in longitude. Several mechanisms contributed to the broad longitudinal spread of SEPs and formation of the energetic particle reservoir, including acceleration at an extended CME-driven shock, particle drifts along the heliospheric current sheet, particle reflection and redistribution caused by the merging of preceding CMEs beyond 1 au, and predominantly cross-field particle transport processes.